The relationship of α-hydroxybutyrate dehydrogenase with 1-year outcomes in patients with intracerebral hemorrhage: A retrospective study - Limin, Zhang; Alsamani, Rasha; Jianwei, Wu; Yijun, Shi; Dan, Wang; Yuehong, Sun; Ziwei, Liu; Huiwen, Xu; Dongzhi, Wang; Xingquan, Zhao; Guojun, Zhang (Frontiers in Neurology, 2022)
Background and aims Cardiac enzymes are recognized as a valuable tool for predicting the prognosis of various cardiovascular diseases. The prognostic value of alpha-hydroxybutyrate dehydrogenase (α-HBDH) in patients with intracerebral hemorrhage (ICH) was ambiguous and not evaluated. Methods Two hundred and thirteen Chinese patients with ICH participated in the study from December 2018 to December 2019. Laboratory routine tests and cardiac enzymes, including α-HBDH level, were examined and analyzed. All the patients were classified into two groups by the median value of α-HBDH: B1 <175.90 and B2 ≥175.90 U/L. The clinical outcomes included functional outcome (according to modified Rankin Scale (mRS) score ≥3), all-cause death, and recurrent cerebro-cardiovascular events 1 year after discharge. Associations between the α-HBDH and the outcomes were evaluated using logistic regression analysis. Univariate survival analysis was performed by the Kaplan–Meier method and log-rank test. Results Of the 213 patients, 117 had α-HBDH ≥175.90 U/L. Eighty-two patients had poor functional outcomes (mRS≥3). During the 1-year follow-up, a total of 20 patients died, and 15 of them had α-HBDH ≥175.90 U/L during the follow-up time. Moreover, 24 recurrent events were recorded. After adjusting confounding factors, α-HBDH (≥175.90) remained an indicator of poor outcome (mRS 3-6), all-cause death, and recurrent cerebro-cardiovascular events. The ORs for B2 vs. B1 were 4.78 (95% CI: 2.60 to 8.78, P = 0.001), 2.63 (95% CI: 0.80 to 8.59, P = 0.11), and 2.40 (95% CI: 0.82 to 7.02, P = 0.11) for poor functional outcomes with mRS ≥ 3, all-cause death, and recurrent cerebro-cardiovascular events, respectively. Conclusion Increased α-HBDH at admission was independently related to poor functional outcome and all-cause mortality in patients with ICH at 1-year follow-up.